Bikeway Networks: A Review of Effects on Cycling. Issue 1 (2nd January 2016) - Buehler, Ralph; Dill, Jennifer
Abstract: Research linking bikeway infrastructure and cycling levels has increased significantly over the last 20 years — with the strongest growth since 2010. The research has evolved from the study of lanes and paths, to include analyses of the role of intersection treatments, and finally to studies that attempt to measure the whole bike network. Most studies suggest a positive relationship between bikeway networks or aspects of the network and cycling levels. Stated and revealed-preference studies suggest a hierarchy of cyclist and non-cyclist preferences may exist, favoring separate paths and/or lanes over cycling on roadways with traffic — particularly with high volumes of fast-moving motorized traffic. Revealed- and stated-route-choice studies indicate that intersections have negative effects on the cycling experience, but that certain features can offset this. The research correlating link and node characteristics to cycling implies that networks of such facilities would have positive effects, though very few empirical studies link complex measures of the network to cycling levels. In spite of an increase in studies and general agreement among findings, several important research gaps remain, including empirical studies using comprehensive network measures and studies of specific facility designs and new types of facilities (including intersection treatments). Improved research methods are necessary, including better sampling, longitudinal studies, greater geographic diversity, and incorporating more control variables, including policies.